Short-Term Blood Pressure Variability in Acute Stroke: Post Hoc Analysis of the Controlling Hypertension and Hypotension Immediately Post Stroke and Continue or Stop Post-Stroke Antihypertensives Collaborative Study Trials. Issue 6 (June 2015) - Manning, Lisa S.; Mistri, Amit K.; Potter, John; Rothwell, Peter M.; Robinson, Thompson G.
Abstract : Background and Purpose—: Short-term blood pressure variability (BPV) may predict outcome in acute stroke. We undertook a post hoc analysis of data from 2 randomized controlled trials to determine the effect of short-term BPV on 2-week outcome. Methods—: Controlling Hypertension and Hypotension Immediately Post Stroke (CHHIPS) was a trial of BP-lowering, enrolling 179 acute stroke patients (onset <36 hours). Continue or Stop Post-Stroke Antihypertensives Collaborative Study (COSSACS) compared a strategy of continuation versus temporarily stopping prestroke antihypertensive therapy in 763 acute stroke patients (onset <48 hours). BPV at baseline (defined as SD, coefficient of variation, variation independent of the mean, and average real variability) was derived from standardized casual cuff BP measures (6 readings <30 minutes). Adjusted logistic regression models were used to assess the relation between BPV and death and disability (modified Rankin scale>3) at 2 weeks. Results—: Seven hundred six (92.5%) and 171 (95.5%) participants were included in the analysis for the COSSACS and CHHIPS data sets, respectively. Adjusted logistic regression analyses revealed no statistically significant associations between any of the included BPV parameters with 2-week death or disability in either study data set: COSSACS, odds ratio SD systolic BP 0.98 (0.78–1.23); CHHIPS, odds ratio SD systolic BP 0.97 (0.90–1.11). Conclusions—: When derived from casual cuff BP measures, short-term BPV is not a useful predictor of early (2 weeks) outcome after acute stroke. Differing methodology may account for the discordance with previous studies indicating long-term (casual BPV) and short-term (beat-to-beat BPV) prognostic value. Clinical Trial Registration—: COSSACS was registered on the International Standard Randomised Controlled Trial Register; URL:http://www.isrctn.com . Unique identifier: ISRCTN89712435. CHHIPS was registered on the National Research Register; URL:http://public.ukcrn.org.uk . Unique identifier: N0484128008. Abstract : Supplemental Digital Content is available in the text.